Burning Refuge: Spiritual and Political Liberation in the Navayana Buddhist Movement - Pontoriero, Eleanor (Journal of International Buddhist Studies, 2025)
This paper discusses how the Theravada Buddhist scriptures in the Pali Canon support B. R. Ambedkar’s Navayana Buddhist movement in their struggle to eradicate caste and gender-based discrimination in the social, political, and legal spheres. Among these teachings are passages that record the stories of low caste and female disciples who free themselves from all fetters, spiritual and political. This paper focuses on the verses of Awakening by early Buddhist nun Puņņikā Therī in the Therī Apadāna and Therīgāthā, recognized for having realized full enlightenment on par with males. An ancestor of Navayana Buddhists, she was born low caste and female and is an inspiration for this movement’s advocacy for the equality of all people in the contemporary context. From the onset, women have actively advocated in this regard for themselves and their communities. Their socially engaged grassroots Buddhist approach emphasizes the inseparable link between spiritual and political liberation on individual and communal levels. The Buddha’s simile in AN 10.51 aptly expresses the impetus for this movement: a wholesome desire for liberation from suffering as a burning fire consuming all obstacles and a refuge, both temporal and ultimate.[1] [1] This article is based on a talk given at the March 2024 Conference: Burning Refuge: Social and Political Liberation, Harvard University, US.